1995
DOI: 10.1016/1044-0305(94)00092-e
|View full text |Cite
|
Sign up to set email alerts
|

Reactive collisions in quadrupole cells. 3: H/D exchange reactions of protonated aromatic amines with ND3

Abstract: The H/D exchange reactions of a variety of protonated aromatic amines with ND3 m the collision cell of a hybrid BEqQ tandem mass spectrometer have been studied. The MH(+) ions were prepared by CH4, t-C4H10, and NH3 chemical ionization (CI) and, for some amines, by fast-atom bombardment (FAB). Evidence is presented that the kinetic energy of the incident ion as well as its internal energy must be dissipated by nonexchanging collisions before exchange occurs, once deactivated the MH(+) ions exchange efficiently,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 48 publications
(70 reference statements)
1
17
0
Order By: Relevance
“…The rate of H/D exchange of the protonated alkylbenzenes was found to be comparable to that of the enolate ions studied previously (26) with the result that we used the maximum indicated pressures (3 x Torr) of deuterated reagent gas that were attainable with the existing experimental configuration. This pressure is about a factor of 10 higher than was used for the exchange of the labile hydrogens of protonated aromatic amines (21) or protonated amino acids (24) with ND,. Since the ionization cross section is expected to be greatest for C2H50D and least for D20 (30), the use of the same indicated pressure means that the actual collision cell pressure was least for the alcohol and greatest for D20; despite the higher D20 pressure the exchange with D20 was the least efficient, as discussed below.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate of H/D exchange of the protonated alkylbenzenes was found to be comparable to that of the enolate ions studied previously (26) with the result that we used the maximum indicated pressures (3 x Torr) of deuterated reagent gas that were attainable with the existing experimental configuration. This pressure is about a factor of 10 higher than was used for the exchange of the labile hydrogens of protonated aromatic amines (21) or protonated amino acids (24) with ND,. Since the ionization cross section is expected to be greatest for C2H50D and least for D20 (30), the use of the same indicated pressure means that the actual collision cell pressure was least for the alcohol and greatest for D20; despite the higher D20 pressure the exchange with D20 was the least efficient, as discussed below.…”
Section: Methodsmentioning
confidence: 99%
“…The incident ion kinetic energy and the pressure of reactant gas in the collision cell are the two major parameters that determine the extent of H/D exchange. Earlier studies (21,24,26) have shown that incident ion energies in the range of 1-5 eV (laboratory scale) give a reasonable extent of exchange with higher ion energies affording better sensitivity because of greater transmission of the incident ion beam; the present experiments were carried out at 3 eV incident ion energy. The method used to establish this ion energy in a reproducible fashion has been presented in detail previously (21,26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When H + is added to aniline under kinetic control, as can be true in chemical ionization (CI) 72 , the protonation site has been suggested to be not necessarily dictated by the proton affinity (PA) 78 . The structure of CI-generated [M + H] + has so far been interrogated by several mass spectrometric techniques 79 -83 , mainly via isotopic labeling followed by collision-induced dissociation (CID) 79 -81 and ion/molecule reactions 82,83 . Based on the behavior of D-isotopologues, these studies have pointed out that CI generates both tautomers, with the predominance of the amino-protonated form 79 -83 .…”
Section: B Site Of Protonation Of Anilinesmentioning
confidence: 99%
“…The chemical incorporation of deuterium followed by ionization has played a major role in the structural characterization of molecules, in gaining information on the mechanisms of chemical or biological reactions, and in the interpretation of mass spectra [1][2][3][4][5][6][7]. Many ionization methods have been used: Electron ionization (EI) [1], chemical ionization (CI) [8 -10], fast atom bombardment (FAB) [11][12][13], thermospray [14,15], particle beam [15], and electrospray ionization (ESI) [3, 16 -25].…”
mentioning
confidence: 99%